Design Of Fuzzy Logic-Based Temperature Control System For PPF Installation Workshop Spaces - Adelia Azzahra; Solly Aryza; Ahmad Dani (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This Paper described design a fuzzy logic-based temperature control system for Paint Protection Film (PPF) installation workshop spaces. PPF installation requires optimal temperature conditions (20-27°C) to ensure proper adhesion, but workshop environments often experience temperature fluctuations that compromise installation quality. The research method uses computational simulation with a modified Mamdani fuzzy logic approach, incorporating more aggressive membership functions, adaptive aggression factors, and integral control. Simulation was conducted with a setpoint of 20°C, initial temperature of 30°C, and duration of 30 minutes. Results show the system successfully achieved a steady-state error of 1.491°C, overshoot of 45.14%, and settling time of 30.0 minutes, meeting validation criteria with steady-state error < 1.5°C. The system maintained temperature within the manufacturer-recommended range for PPF installation. The research concludes that modified fuzzy logic control strategies effectively enhance system performance for specific PPF workshop applications. The main contribution is the development of a control system tailored to the specific requirements of PPF workshop environments, filling a research gap in intelligent control system applications for this context.